Perceived Factors Influencing the Equity of Assessment in Inclusive Secondary Classrooms - Rastegar, Babak; Salavati Nooshabadi, Mitra (Assessment and Practice in Educational Sciences, 2023)
This study aimed to explore the perceived factors influencing the equity of assessment practices in inclusive secondary classrooms from the perspective of teachers. A qualitative research design was employed to investigate teachers' experiences with inclusive assessment. Data were collected through semi-structured interviews with 20 secondary school teachers from inclusive classrooms in Tehran, selected using purposive sampling. Interviews continued until theoretical saturation was achieved. The interview protocol focused on pedagogical strategies, institutional constraints, and socio-emotional dynamics related to assessment equity. All interviews were transcribed verbatim and analyzed thematically using Braun and Clarke’s framework. Nvivo software was utilized to manage, organize, and code the data systematically. Thematic analysis revealed three overarching themes: (1) pedagogical and instructional factors, (2) institutional and policy constraints, and (3) socio-emotional and cultural dynamics. Subthemes included differentiated assessment strategies, clarity of criteria, feedback practices, standardized testing pressures, limited professional development, and the emotional impact of assessment on learners. Teachers reported tensions between inclusive intentions and systemic constraints, such as national exams, resource shortages, and ambiguous policies. While some educators adopted student-centered, culturally responsive practices, others struggled due to inadequate support and ingrained deficit beliefs. Participants emphasized the role of student agency, emotional safety, and teacher mindset in promoting assessment equity. The study highlights the multifaceted nature of assessment equity in inclusive classrooms, shaped by intersecting pedagogical, institutional, and socio-cultural factors. To support equitable assessment, systemic reforms are needed, including improved teacher training, flexible assessment policies, and greater incorporation of student voice. Addressing these challenges is essential for realizing the full potential of inclusive education and ensuring that all learners can demonstrate their knowledge in fair and meaningful ways.